An Overview of DNA Methylation Indicators for the Course of Oral Precancer - Wenjing Wang; Wei Li; Hongyi Zhang (Applied Bionics and Biomechanics)
DNA methylation is a physiologically epigenetic alteration that happens when a methyl group is introduced to a CpG dinucleotide in the gene-regulating sequence of DNA. However, the majority of oral cancers have a well-defined precancerous stage; there are few clinical and morphological parameters for detecting and signalling the progression of precancerous to malignant tumours. DNA methylation forms are dynamic and reversible, allowing them to adjust to environmental or therapeutic changes. We did an extensive investigation to compile the data supporting aberrant DNA methylation forms as a possible biomarker for prediction. According to two longitudinal studies, p16 hypermethylation was considerably higher in precancerous lesions that progressed to cancer than in lesions that shrank. Most of the studies examined for this study were tiny cross-sectional research with scant validation and inadequately specified control groups. Existing evidence suggests that DNA methylation sequences can be relevant as a diagnostic biomarker for OPS development; however, sample size and research design restrictions make it difficult to draw definitive conclusions. Strong studies, including extensive epigenome-wide methylation scans of OPS with longitudinal monitoring, are necessary in this study in order to corroborate the recently discovered signals and discover new risk loci and disease progression molecular pathways.